Numerical and experimental study of the motion of a sphere in a communicating vessel system subject to sloshing - Zamora, Esteban (2019)
The purpose of this work is twofold: to present a computational strategy to simulate the dynamics of a rigid sphere during water sloshing and to validate the model with original experimental data. The numerical solution is obtained through the coupling between a two-fluid Navier-Stokes solver and a rigid solid dynamics solver, based on a Newton scheme. A settling sphere case reported in the literature is first analyzed to validate the numerical strategy by ascertaining the settling velocity. In addition, an experiment is carried out based on a sphere submerged into a communicating vessel subjected to sloshing. Experimental data are captured using image processing and statistically treated to provide sphere dynamics quantitative information. The effects of different classical models used to describe drag coefficients, added mass, and wall effects are considered in the study to evaluate their influence on the results. The numerical model provides results that are consistent with the physical data, and the trajectory analysis shows good agreement between the simulations and the experiments.